INTERNATIONAL TOURISM DEVELOPMENT FACTORS - PETRUSHENKO, YURIY; ZHURAVKA, FEDIR; MAREKHA, IRYNA; NOVGORODCEVA, MARIYA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
In the article, the authors analyze the scope of international tourism development factors based on factological and statistical grounds. It was proven in the article that on the macro-level tourist markets can be grouped into national and oversea ones. The classification of the national markets implies their division into highly-intensive markets (USA, Germany, Great Britain, etc.), stabilized markets (Spain, Greece, Turkey, Poland, etc.), reformed markets (Bulgaria, Romania, Ukraine, China, etc.), ant accumulated markets (India, Tunis, Egypt, Cuba, etc.). The basic factors affecting the international tourist market include static (climate, natural resources, cultural heritage, etc.) and dynamic ones (population, urbanization, wealth, family, leisure, income, spending, technological advancement, international conflicts and their resolution, etc.). In the article, special attention is paid to the analysis of the dynamic factors of international tourism development, social and economic ones in particular. The presence of positive factors in the country promotes favorable conditions for enhancing its tourist attractiveness on the international level. It was found out that positive factors increase the inflows of tourists for the specific regions (Brazil, France, Great Britain, Germany, Finland, Sweden, Cyprus, Israel, and U.A.E.). On the national level, the following factors are crucial for the development of tourist industry: natural resources, politics, population and its well-being, cultural heritage and rich history. It was revealed, that in Ukraine tourist business is internationally-oriented, which has both pros and cons for the national economy. In the article, the authors presented a matrix with positive (catalysts) and negative (inhibitors) factors affecting tourist business in Ukraine. Among the positive drivers are large contribution to the national economy and state financial support. At the same time, imperfect infrastructure and lack of legal regulations can be referred to the negative factors. It was stressed in the article that drastic measures should be undertaken in order to increase social and economic performance of national tourist business in Ukraine and increase it international image.